Ответ:
Пошаговое объяснение:
4) (8а² - 2ab) - (4ac - bc) =
2a(4a - b) - c(4a - b) =
(4a - b) * (2a - c)
5) (2b³ - 7b²c) - (4b - 14c) =
b²(2b - 7c) - 2(2b - 7c) =
(2b - 7c) * (b² - 2)
6) (6x^5 + 4x²y²) - (9x³y + 6y³) =
2x²(3x³ + 2y²) - 3y(3x³ + 2y²) =
(3x³ + 2y²) * (2x² - 3y)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
4) (8а² - 2ab) - (4ac - bc) =
2a(4a - b) - c(4a - b) =
(4a - b) * (2a - c)
5) (2b³ - 7b²c) - (4b - 14c) =
b²(2b - 7c) - 2(2b - 7c) =
(2b - 7c) * (b² - 2)
6) (6x^5 + 4x²y²) - (9x³y + 6y³) =
2x²(3x³ + 2y²) - 3y(3x³ + 2y²) =
(3x³ + 2y²) * (2x² - 3y)